ANALISIS FRAMING PEMBERITAAN PERTANDINGAN INDONESIA VS MALAYSIA DI PEREMPAT FINAL THOMAS CUP 2020 (ANALISIS FRAMING PADA KOMPAS.COM DAN THESTAR.COM.MY EDISI OKTOBER 2021) - Ina Barina (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2022)
The purpose of this research is to give description about how Kompas.com and Thestar.com.my did framing at news about match Indonesia vs Malaysia in Thomas Cup 2020. Research’s methode that used in this research is descriptive with qualitative approach. Based on the result and study in this research, Kompas.com and Thestar.com.my have their own way to frame news about match Indonesia vs Malaysia in Thomas Cup 2020. Kompas.com created a framing with view about Indonesia’s won above Malaysia was really important and gave positive claim to Indonesian Thomas team. Meanwhile, Thestar.com.my served original news and have no specific claim about Malaysian goodness or Indonesian worst. Based on journalistic ethic code, Kompas.com as one of biggest media in Indonesia didn’t give a fair news. Be different, Thestar.com.my did a true role of media, but their short headline is less informative and had not represented news content inside.